Population-based analysis of the epidemiology of the surgical correction of hyperhidrosis in 1,216 patients over 11 years: a cross-sectional study - Silva, Marcelo Fiorelli Alexandrino da; Louzada, Andressa Cristina Sposato; Teivelis, Marcelo Passos; Stabellini, Nickolas; Leiderman, Dafne Braga Diamante; Campos, José Ribas Milanez de; Amaro Junior, Edson; Wolosker, Nelson (São Paulo Medical Journal, 2022)
BACKGROUND: Endoscopic thoracic sympathectomy is the definitive surgical treatment for hyperhidrosis and a nationwide study has suggested that cultural and socioeconomic factors play a role in the numbers of operations performed. Thus, there is a need to evaluate local data in order to understand the local epidemiology and trends in hyperhidrosis treatment. OBJECTIVE: To study the epidemiology of sympathectomy for treating hyperhidrosis in São Paulo, the largest city in Brazil. DESIGN AND SETTING: Population-based retrospective cross-sectional study. METHODS: Data on sympathectomies for treating hyperhidrosis between 2008 and 2018 were assessed from the database of the Municipal Health Department of São Paulo, Brazil.RESULTS: 65.29% of the patients were female, 66.2% were aged between 20 and 39 years and 37.59% had registered with addresses outside São Paulo. 1,216 procedures were performed in the city of São Paulo from 2008 to 2018, and 78.45% of them were in only two public hospitals. The number of procedures significantly declined over the years (P = 0.001). 71.63% of the procedures were associated with 2-3 days of hospital stay, only 78 intensive care unit days were billed and we did not observe any intra-hospital death. CONCLUSION: The profile of patients operated on in São Paulo (young women) is similar to that described in other populations. Sympathectomy is a very safe procedure, with no mortality in our series. There was a decreasing trend in the number of surgeries over the years.